2014
DOI: 10.1002/jnr.23424
|View full text |Cite
|
Sign up to set email alerts
|

Blast‐Induced tinnitus and spontaneous firing changes in the rat dorsal cochlear nucleus

Abstract: Exposure to high-pressure blast shock waves is known to cause tinnitus. Although the underlying mechanisms may involve damage to structures in the ear and/or direct brain impact, which triggers a cascade of neuroplastic changes in both auditory and nonauditory centers, it remains unclear how the induced neuroplasticity manifests neurophysiologically. This study investigates the influence of blast exposure on spontaneous firing rates (SFRs) in the dorsal cochlear nucleus (DCN) and its time course in rats with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 69 publications
8
26
1
Order By: Relevance
“…As shown in our recent study (see Figures 1-2 in (Luo et al, 2014b), there were nine tinnitus positive rats at one day following blast exposure, six tinnitus positive and three tinnitus negative rats at one month after blast, and four tinnitus positive and five tinnitus negative rats at three months after blast. Significant hearing threshold elevations were found in the exposed ears of rats at one day after blast, while rats exhibited threshold recovery at one and three months after blast exposure.…”
Section: Resultssupporting
confidence: 72%
“…As shown in our recent study (see Figures 1-2 in (Luo et al, 2014b), there were nine tinnitus positive rats at one day following blast exposure, six tinnitus positive and three tinnitus negative rats at one month after blast, and four tinnitus positive and five tinnitus negative rats at three months after blast. Significant hearing threshold elevations were found in the exposed ears of rats at one day after blast, while rats exhibited threshold recovery at one and three months after blast exposure.…”
Section: Resultssupporting
confidence: 72%
“…Quantitative analysis indicates that AI neurons in the blast-exposed animals had higher thresholds than those of the sham-exposed animals (one-way ANOVA, F 1,8 = 5.97, p = 0.040; Figure 3). This is consistent with a high ABR threshold in the blast-compared to the sham-exposed animals (Luo et al, 2014b).…”
Section: Resultssupporting
confidence: 85%
“…Therefore, different scientists used their own criteria to interpret gap detection data and often these criteria can vary dramatically from one lab to the other. Table 1 summarizes the main characteristics of studies that have used the GPIAS paradigm across species, namely, rats ( 12 , 16 34 ), mice ( 35 41 ), guinea pigs ( 42 45 ), gerbils ( 46 ), hamsters ( 47 ), and humans ( 48 – 52 ).…”
Section: Advantages and Problems With The Gpias Methodsmentioning
confidence: 99%
“…However, the extensive consequential damage resulting from blast exposure would make the development of such a tinnitus animal model very challenging. For these reasons, this model is only being developed in one laboratory ( 32 34 , 56 ). These studies have suggested that after a single or multiple unilateral blast exposures animals typically developed gap detection deficits, which are evident across a wide range of sound frequencies.…”
Section: Tinnitus Inductionmentioning
confidence: 99%